Next generation sequencing in early diagnosis of pneumocystis jirovecii pneumonia after chemotherapy: a case report - Zheng, Donghua; Chen, Kai; Xiao, Fang; Liu, Na (International Journal of Research in Medical Sciences, 2019)
The incidence of Pneumocystis pneumonia is increasing in immunosuppressive patients. How to diagnose and treat Pneumocystis pneumonia in the early stage has become an important issue for clinicians. The development of Next-generation Sequencing (NGS) provides technical support for the diagnosis of Pneumocystis pneumonia. Case report: A 14-year-old male patient was diagnosed with T lymphoblastoma and treated with chemotherapy. After chemotherapy, the patient developed bone marrow suppression and was complicated with severe pneumonia. He was given endotracheal intubation and ventilator assisted respiration. Samples of patients' alveolar lavage fluid were obtained, and Next-generation Sequencing (NGS) was used for diagnosis, confirming the pathogen as Pneumocystis jiroveci, which was treated by TMP/SMX. The patient's condition gradually improved, and was finally removed from ventilator and endotracheal tube. Pneumocystis jiroveci is a common opportunistic pathogen in immunosuppressive patients, and Next-generation Sequencing (NGS) can be used for rapid diagnosis of Pneumocystis pneumonia, thus improving the clinical therapeutic effect.